2001
DOI: 10.1163/156856201316883467
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of corneal epithelial cells to cell adhesion peptide modified pHEMA surfaces

Abstract: Epithelialization of a corneal implant is a desirable property. In this study we compared surface modification of poly (2-hydroxyethyl methacrylate) (pHEMA) with the cell adhesion peptides RGDS and YIGSR. Various parameters in the tresyl chloride activation and modification reactions were considered in order to maximize surface coverage with the peptide including tresyl chloride reaction solvent. tresyl chloride reaction time, tresyl chloride concentration, peptide concentration, and peptide reaction pH. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Surprisingly, the adsorption of laminin to the surfaces prior to culture, while resulting in an increase in the epithelial cell coverage relative to the controls, did not provide the dramatic effect expected based on our previous results. 14,15 The effect of the TGF-␤2 and its activity on the surface is clearly demonstrated by the increases in epithelial cell coverage on all surfaces with TGF-2 (relative to the aminated controls) and more importantly by the significant decrease in coverage in the presence of anti-TGF-␤ under serum-free conditions.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, the adsorption of laminin to the surfaces prior to culture, while resulting in an increase in the epithelial cell coverage relative to the controls, did not provide the dramatic effect expected based on our previous results. 14,15 The effect of the TGF-␤2 and its activity on the surface is clearly demonstrated by the increases in epithelial cell coverage on all surfaces with TGF-2 (relative to the aminated controls) and more importantly by the significant decrease in coverage in the presence of anti-TGF-␤ under serum-free conditions.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…Stromal cells were cultured in either Dubellco's Modified Eagle Medium (DMEM) (Gibco BRL Life Technologies, Burlington, ON) supplemented with insulin-transferrin-selenium (1 mL/L) (ITS) and gentamycin or DMEM supplemented with ITS, gentamycin, and 10% fetal bovine serum (FBS). Additional surfaces were preadsorbed with laminin based on positive results with YIGSR and related peptides in our previous work 14,15 for a period of 2 h prior to culture under serum-free conditions. Samples were examined on a daily basis for cell attachment, spread, and proliferation.…”
Section: Cell Culture Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hydrogels characteristically have low protein adsorption and therefore low native cell interactions, many studies have examined addition of biological molecules to promote cell interactions. These include addition of adhesion peptides such as RGD and YIGSR [142][143][144][145][146] which enhance interactions of specific cell types, polysaccharides such as heparin that are able to present growth factors [147,148], and growth factors themselves [149,150].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Cell adhesion peptides, including RGD, YIGSR, and a novel collagen peptoid Gly-Pro-nLeu, have also been studied, but these peptide/peptoid modifications have produced only modest increases in the rate of epithelialization. [37][38][39][40][41] To date, although a few replacement materials with either coating and/or direct attachment of biological factors (both proteins and peptides) to their surfaces have had some short-term success in maintaining a somewhat normal epithelial layer, long-term analysis (up to 8 years) has shown that the density of the epithelial layer is not maintained. [42][43][44][45] We have investigated the chemical tethering of extracellular matrix proteins and peptides with epithelial cell-surface adhesion binding activities to a hydrogel surface.…”
Section: Introductionmentioning
confidence: 99%